The Concept of Habituation Learning in Developing Students' Talents, Interests, and Creativity in Dance Art Learning at Andhe-andhe Lumut Art Studio Kediri - Setyowati, Putri Jania; Muhajir, Muhajir; Wahyuningtyas, Sri (UNDIKMA, 2023)
The background of this research was that education in contemporary Indonesia used to emphasize academic abilities. Society used to consider the acquisition of grades in a subject and use it as a measure of success in learning. Additionally, the preservation of cultural heritage and the fundamental cultural data statistics in East Java used to be uneven. This research aimed to: 1) Analyze the concept of habituation learning; 2) Analyze the implementation of the habituation concept in developing talents, interests, and creativity. This research used a qualitative method by observing events that occurred in the field, noting what happened, analyzing documents found in the field, creating transcripts of field findings, and generating a detailed research report. The research was conducted at Andhe-andhe Lumut Art Studio Kediri, observing all the learning activities. Data sources for this research were informants, including studio trainers, studio owners, studio users, and studio students; places and events; relevant studio-related documents. Data were collected through observation, interviews, and documentation. The research resulted the following findings: 1) The concept of habituation was carried out in six stages: thinking, recording, repetition, storage, repetition again, habit; 2) Talent was supported by factors like navitis, empirical, convergence; 3) Interest was affected by factors like attention, pleasure, willingness; 4) Creativity was executed in four stages: preparation, incubation, illumination, confirmation, which encompassed the ability to create dance floor patterns, create movements, and produce new dance works